Dawn of autonomous vehicles: review and challenges ahead - Sousa, Nuno (2018)
This paper reviews the state of the art on autonomous vehicles as of 2017, including their impact at socio-economic, energy, safety, congestion and land-use levels. This impact study focuses on the issues that are common denominators and are bound to arise independently of regional factors, such as (but not restricted to) change to vehicle ownership patterns and driver behaviour, opportunities for energy and emissions savings, potential for accident reduction and lower insurance costs, and requalification of urban areas previously assigned to parking. The challenges that lie ahead for carmakers, law and policy makers are also explored, with an emphasis on how these challenges affect the urban infrastructure and issues they create for municipal planners and decision makers. The paper concludes with strengths, weaknesses, opportunities, and threats analysis that integrates and relates all these aspects.